Comparación entre dos poblaciones de Acanthina brevidentata (Gastropoda: Mollusca) en dos zonas rocosas de Playa Panamá, Guanacaste, Costa Rica - Madrigal Castro, Eduardo (1984)
A comparative study between two Acanthina brevidentata (Woods, 1828) populations from July to September, 1982 in Playa Panamá, Bahía Culebra, Guanacaste, Costa Rica, showed different regression and correlation values in total weight, aperture length, total width and totallength between the two populations. The horizontal distribution along the surface transect in the intertidal zone showed a gradual increase in the number of individuals for one population, whereas it was irregular in the other; spatial dispersion was regular in one and contagious in the other.